A taxonomic review of the genus Axinoscymnus Kamiya, with descriptions of three new species (Coleoptera, Coccinellidae) - Peng, Feng; Xie, Xiufeng; Peng, Zhengqiang; Wang, Xingmin; Chen, Xiaoshen (Zootaxa, 2022)
Eleven species of the genus Axinoscymnus Kamiya are revised, and additional three new species are described: Axinoscymnus pingxiangicus Peng et Chen sp. n., Axinoscymnus gongxinensis Peng et Chen sp. n. and Axinoscymnus hamulatus Peng et Chen sp. n. The genus Axinoscymnus is recorded from Nepal for the first time. Several species are also newly reported from the following countries: Axinoscymnus puttarudriahi Kapur et Munshi for China, Laos and Nepal, Axinoscymnus macrosiphonatus Hoàng for China and Laos, Axinoscymnua navicularis Ren et Pang for Laos and Nepal, Axinoscymnus cardilobus Ren et Pang and Axinoscymnus nigripennis Kamiya for Laos. Nomenclatural history, diagnoses, detailed description, illustrations, and distribution for most species have been provided. A key to the species of this genus is also given.